PROBLEM INTERPRETACJI ŹRÓDEŁ A STATUS DZIECKA W ŁONIE KOBIETY (NASCITURUS) - Waldstein, Wolfgang (Zeszyty Prawnicze, 2017)
A Problem of Interpretation of a status of a Child in a Woman’s Womb (nasciturus) Summary The author in his research often encountered citations of little parts of the sources, taken out of context, as a confirmation of the prior adopted thesis. This also happened with respect to a text regarding an unborn child, described by Ulpian as mulieris portio vel viscerum (D. 25,4,1,1). According to some researchers this description is to indicate that a child, as a part of a woman’s body, does not have a separate legal status. The author shows that from the context of the quoted text and many other sources (e. g. Cic. pro Cluent. 31; Gaius - G. 1,89 i 1,147; Iulianus - D. 2,1,5,25; D. 38, 16,6; Marcianus - D. 1,5,5,3 i Paulus - D. 1,5,7) it transpires that a lot of attention was given to an unborn child and a protection of his rights, which proves that he was treated as a separate and independent subject of law.